Entrepreneurship Learning Management in Improving the Independence of Vocational School Students - Anton Anton; Iim Wasliman; Agus Sudarya; Yosal Iriantara (International Journal of Nusantara Islam, 2021)
This study examines the management of entrepreneurial learning in increasing student independence in SMK (Multi Case Study at Mutiara Qolbu Vocational School and Ar Rahmah Vocational School in Cianjur Regency). Approach The research carried out in writing this article is to use a descriptive analytical method with a qualitative approach. The use of this approach is adapted to the main objectives of the study, namely to describe and analyze. The results of this study conclude that, the Implementation of Entrepreneurial Learning Management in Improving Student Independence at SMK Ar Rahmah Cianjur and SMK Mutiara Qolbu Cianjur in an effort to prepare productive entrepreneurship teachers is optimized by various government regulatory policies so that there is an increase in student independence. However, there are problems in the management of entrepreneurial learning regarding efforts to improve the quality of entrepreneurship. First, the quality of student entrepreneurship standards has not been standardized nationally. Second, the quality of product marketing techniques is still centralized on productive entrepreneurship teachers. This means that product marketing techniques have not collaborated with the head of the business unit and the head of the expertise. Third, the quality of compiling a business plan is too heavy and congested.